Impact of emotional exhaustion and locus of control on psychological distress in parents of children with neurodevelopmental disabilities - Usman, Talala; Imtiaz, Rooma; Zaidi, Syeda Saba (Academic Journal of Psychology and Counseling, 2025)
In Pakistan, parents’ mental health is a crucial and under-researched topic, especially for parents of children with neurodevelopmental disorders (NDDs) like intellectual disabilities (ID), attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD). The aim of this study was to investigate the association between these variables and psychological distress in parents of children with neurodevelopmental disorders, compare the scores of mothers and fathers, and ascertain whether locus of control and emotional exhaustion can predict psychological distress. The study used validated tools, namely the Kessler Psychological Distress Scale, Parental Locus of Control Scale, and Parental Stress Scale, to measure these variables in a sample of 180 parents (90 mothers and 90 fathers) selected from Sehat Medical Complex in Lahore. The results showed that psychological distress, locus of control, and emotional exhaustion are significantly correlated. While fathers showed a stronger internal locus of control, mothers reported higher levels of psychological distress and emotional exhaustion. Psychological distress is positively predicted by emotional exhaustion and negatively predicted by locus of control, according to regression analysis. The study discussed focused interventions to reduce parental stress and enhance coping strategies, as well as the gendered aspects of caregiving responsibilities. This study also offers insights into strategies for improving parental well-being and reducing detrimental effects on child development.